Report of the third Asian Prostate Cancer study meeting - Bannakij Lojanapiwat (2018)
© 2018 The Asian Prostate Cancer (A-CaP) study is an Asia-wide initiative that was launched in December 2015 in Tokyo, Japan, with the objective of surveying information about patients who have received a histopathological diagnosis of prostate cancer (PCa) and are undergoing treatment and clarifying distribution of staging, the actual status of treatment choices, and treatment outcomes. The study aims to clarify the clinical situation for PCa in Asia and use the outcomes for the purposes of international comparison. Following the first meeting in Tokyo in December 2015, the second A-CaP meeting was held in Seoul, Korea, in September 2016. This, the third A-CaP meeting, was held on October 14, 2017, in Chiang Mai, Thailand, with the participation of members and collaborators from 12 countries and regions. In the meeting, participating countries and regions presented the current status of data collection, and the A-CaP office presented a preliminary analysis of the registered cases received from each country and region. Participants discussed ongoing challenges relating to data input and collection, institutional, and legislative issues that may present barriers to data sharing, and the outlook for further patient registrations through to the end of the registration period in December 2018. In addition to A-CaP–specific discussions, a series of special lectures were also delivered on the situation for health insurance in the United States, the correlation between insurance coverage and PCa outcomes, and the outlook for robotic surgery in the Asia-Pacific region. Members also confirmed the principles of authorship in collaborative studies, with a view to publishing original articles based on A-CaP data in the future.